Domestic macroeconomic conditions and inflow of workers' remittances in labour-sending Asian countries - Ngoma, Abubakar Lawan; Ismail, Normaz Wana; Law, Siong Hook (Universiti Malaysia Sarawak, 2018)
Simple theoretical consideration suggests that the flows of workers’ remittances ought to be partly driven by domestic macroeconomic indicators. However, empirical research seeking to support this claim has produced mixed results. In this paper, using a Pooled Mean Group (PMG) estimator on panel data from 15 labour-sending Asian countries during the period of 1984-2010, further evidence is produced on the effects of domestic macroeconomic factors on inflows of workers’ remittances. In particular, factors such as interest rate differential between migrant home and destination country, exchange rate depreciation, and financial sector development favourably induce remittance flows from migrant workers abroad. Conversely, workers’ remittances respond negatively to domestic political and/or economic instability.